Podocarpus Aphid (suggested common name) Neophyllaphis podocarpi Takahashi (Insecta: Hemiptera: Aphididae) - Eleanor F. Phillips; Jennifer L. Gillett-Kaufman (EDIS)
The podocarpus aphid, Neophyllaphis podocarpi Takahashi, is a pest of Podocarpus species in Florida, namely the nonnative ornamental shrub Podocarpus macrophyllus (common names include bigleaf podocarpus, kusamaki, podo, Japanese yew, and southern yew) (Stamps no date). The podocarpus aphid is recognizable by its blueish purple color (Figure 1). First found in Florida in Miami in 1968, this invasive aphid can now be found anywhere in Florida where the genus Podocarpus is grown (Brown and Mannion 2014). This document is EENY690, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date November 2017. Revised March 2021.